NAVIGATING INNOVATION HORIZONS: A SYSTEMATIC LITERATURE REVIEW ON LEADERSHIP TRANSFORMATION AND TECHNOLOGICAL COMPETENCE IN INDUSTRIAL MANAGEMENT - Tamrin Reni, Agus; Sinaga, Poltak (Penerbit Lafadz Jaya, 2024)
The integration of green concepts into Industry 4.0 management significantly influences the reshaping of strategies and policies pertaining to leadership and technological competence. Effective green industrial management necessitates leaders who prioritize industrial environmental sustainability and possess proficiency in green technology. This systematic literature review aims to present a comprehensive overview of leadership and technological competence concepts and practices within the context of green industrial management. Employing a structured review method, the framework of this literature review provides insights into the transformative potential of green leadership on both human resources' green performance and the overall industrial environment. The study highlights the imperative for green leaders to enhance their proficiency in green technology to foster sustainable green innovation. The implications drawn from this research offer valuable guidance for green industry managers, aiding them in formulating strategies and policies that foster leadership transformation and enhance green technological competence within the industrial landscape.